2003
DOI: 10.1034/j.1600-0676.2003.00841.x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance/β‐cell function and serum ferritin level in non‐diabetic patients with hepatitis C virus infection

Abstract: Insulin resistance was connected with impaired glucose tolerance and the severity of liver diseases in non-diabetic patients with HCV infection. Iron overload may be responsible for insulin resistance, or vice versa. Pancreatic beta-cell function was unrelated to the patients' serum ferritin levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 22 publications
5
16
1
1
Order By: Relevance
“…To our knowledge, this is the first report that describes the relationship between insulin resistance and Zn deficiency in patients with CH-C. Previously, Furutani and colleagues revealed that insulin resistance was characterized by iron accumulation in the liver (19). We confirmed the correlation between insulin resistance and iron overload in patients with ch-c and postulated that iron overload may derive from Zn deficiency.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…To our knowledge, this is the first report that describes the relationship between insulin resistance and Zn deficiency in patients with CH-C. Previously, Furutani and colleagues revealed that insulin resistance was characterized by iron accumulation in the liver (19). We confirmed the correlation between insulin resistance and iron overload in patients with ch-c and postulated that iron overload may derive from Zn deficiency.…”
Section: Discussionsupporting
confidence: 75%
“…Zn deficiency has been shown to result in attenuation of antioxidative properties and thereby a significant elevation in the serum ferritin level, which corresponds to iron accumulation in the liver. iron overload in the liver eventually evokes insulin resistance (19), as well as necroinflammation (30) in the liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin resistance, a precursor to the development of type 2 DM, has been shown to be higher in HIV/HCV-coinfected patients and HCVmonoinfected controls compared with HIV-monoinfected patients [17]. HCV-monoinfected patients without cirrhosis have also been shown to have insulin resistance, which increases with fibrosis and may be mediated by cytokines [18,[29][30][31]. A biologically plausible mechanism for insulin resistance in HCV infection was shown in a transgenic murine model that expressed HCV core protein.…”
Section: Discussionmentioning
confidence: 99%
“…Na hepatite C diversos estudos têm demonstrado a associação entre RI e níveis elevados de ferritina, mesmo quando pacientes diabéticos são excluídos da análise (18,19) . Entretanto, tem sido observado que a ferritina medida no sangue periférico está associada à presença de síndrome metabólica, tanto na população geral quanto entre diabéticos (30) .…”
Section: Mecanismos De Ri Na Hepatite Cunclassified